Prestasi Belajar Ditinjau dari Kemandirian Belajar dan Persepsi Terhadap Keterampilan Mengajar Dosen Pada Mata Kuliah Dasar Akuntansi Keuangan I Mahasiswa Program Studi Pendidikan Akuntansi Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta Angkatan 2014/2015 - Saputra, Derino Ady; , Drs. Sudarto, M.M (2015)
Derino Ady Saputra, A210110077. Essay. Accounting Education Studies Program, the Faculty of Education, University of Muhammadiyah Surakarta. July 13th, 2015 The purpose of this study was to determine: 1) the influence of independent learning on learning achievement in the subject Financial Accounting Basics 1 student of 2014/2015, 2) influence perception of faculty teaching skills terhdap learning achievement in the subject Financial Accounting Basics 1 student of class 2014 / 2015, 3) the influence of independent learning and perception of the teaching skills of lecturers on academic achievement. This research method is quantitative research associative.The population in this study were students of Accounting Education Surakarta Muhammadiyah University 2nd half .Teknik 201/2015 forces with proportional sampling of non-random sampling technique incidental. Data collection technique used questionnaire method and the method of documentation. Ujiprasyarat use ujinormalitas analysis, and multiple linear regression test. Data were analyzed using t test and f.Results of the data analysis and discussion concluded that: 1) There is the influence of independent learning basic learning achievement tehadap Financial Accounting I Based on t test was obtained, t count> t table = 2.529> 1.984 and the significance value of 0.05, which is 0.013, 2) There is a perception influence teaching skills lecturer on the learning achievement of Financial Accounting I Basic Based on t test was obtained, t count> t table = 3.373> 1.984 and the significance value of 0.05, which is 0.001, 3) There is an effect independent learning and perception of the faculty teaching skills learning achievement terhdap Basic Financial Accounting I Based f test obtained value of F <F table = 18.593 <3.00 4) Variable independent learning contribute effectively amounted to 8.5792%, the variable perception of the teaching skills of lecturers contribute effectively amounted to 12.4982% 5) Variable learning independence gives the relative contribution of 40.6597%, variable perceptions of the teaching skills of lecturers provide relative contribution of 59.2331%. Keywords: Independence learning, perception of the teaching skills of lecturers, Achievement